Retinal morphological changes in non-infectious uveitis in rabbits experimentally treated with citicoline versus non-treated rabbits (Ukrainian Journal of Ophthalmology, 2024)
Purpose: To identify retinal morphological changes in a model of non-infectious anterior and intermediate uveitis and to assess the efficacy of experimental neuroprotective citicoline therapy in the treatment of the disease.Material and Methods: Forty rabbits were divided in two experimental groups, the non-treatment group (18 non-treated rabbits) and treatment group (22 rabbits treated with the neuroprotector). A horse serum rabbit model was used for inducing uveitis. Histological structure of the retina was assessed on days 33 to 54 after the onset of uveitis.Results: In the non-treatment group, there were retinal areas exhibiting marked destructive changes (sites of edema and disorganization in the inner nuclear layer, tractions between the retina and vitreous, reduced numbers of neuronal layers in the nuclear layers, and reduced numbers of ganglion cells) as well as areas of relatively well-preserved retina. At late time points after the onset of uveitis, animals treated with citicoline exhibited an almost normal retinal structure.Conclusion: Horse serum-induced non-infectious anterior and intermediate uveitis contributed to retinal neurodegenerative changes, but uveitic animals treated with the neuroprotector for 33-54 days exhibited only minor neurodegenerative changes.
Keywords: retina; non-infectious uveitis; neurodegeneration; neuroprotection; uveitis model; pathogenesis